2019
DOI: 10.3390/plants8120597
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis of Tephrosia vogelii across East Africa Reveals Three Chemotypes that Influence Its Use as a Pesticidal Plant

Abstract: Tephrosia vogelii is a plant species chemically characterized by the presence of entomotoxic rotenoids and used widely across Africa as a botanical pesticide. Phytochemical analysis was conducted to establish the presence and abundance of the bioactive principles in this species across three countries in East Africa: Tanzania, Kenya, and Malawi. Analysis of methanolic extracts of foliar parts of T. vogelii revealed the occurrence of two distinct chemotypes that were separated by the presence of rotenoids in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Insecticidal activities may not completely rely on rotenone. In the same study [ 112 ], chemotype 1 contained deguelin as the major rotenoid along with tephrosin, and rotenone as a minor component. As mentioned above, extracts from chemotype 1 plants showed insecticidal activities, meaning deguelin plays a critical role in control of insect pests.…”
Section: Concerns Over the Use Of Tephrosia Spementioning
confidence: 98%
See 1 more Smart Citation
“…Insecticidal activities may not completely rely on rotenone. In the same study [ 112 ], chemotype 1 contained deguelin as the major rotenoid along with tephrosin, and rotenone as a minor component. As mentioned above, extracts from chemotype 1 plants showed insecticidal activities, meaning deguelin plays a critical role in control of insect pests.…”
Section: Concerns Over the Use Of Tephrosia Spementioning
confidence: 98%
“…Additionally, distinct chemotypes or variants occur in T. vogelii . Chemical analysis of plant material across Malawi identified two distinct chemotypes, one containing rotenoids for their biological activity against insects [ 111 , 112 ] and the other was characterized by flavones, flavanones, and flavonols [ 18 ]. Subsequent bioassays revealed that insecticidal activities of chemotype 1 were due to the presence of rotenoids, including deguelin, dehydrodeguelin, rotenone, and tephrosin; while the flavonoids in chemotype 2 were inactive [ 39 ] and had little active against insects.…”
Section: Concerns Over the Use Of Tephrosia Spementioning
confidence: 99%
“…Initial plant screening was carried out with ten pesticidal plant species: A. indica, O. basilicum, N. tabacum, C. citratus, T. vogelii, A. vera, L. camara, T. emetica, V. amygdalina and L. javanica. Considerable phytochemical and efficacy knowledge was recorded by our group and others on all the material used of these species [10,15,17,18,20,24,[32][33][34][35][36][37] which were sourced from the same locations with samples from four locations around Mitundu, Lilongwe District, Malawi combined to control for potential chemical variation across space [37,38]. The leaves of all plant species were collected from the wild from these known locations.…”
Section: Plant Materials Collection and Extract Preparationmentioning
confidence: 99%
“…This variation was thus based on the profiles of the flavonoids. Additionally, recent reports have indicated three chemotypes of T. vogelii materials from East Africa (Kenya and Tanzania) through phytochemical analysis [8]. These variations in the phytocompounds would affect the pesticidal activities of these plants pausing limitation to their use which would slow their adoption.…”
Section: Introductionmentioning
confidence: 99%